Історія розвитку геофізичних методів розвідки корисних копалин у Західному реґіоні України - Чебан, Василь; Лящук, Дмитро (НТШ, 2007)
There is distinguished three stages in the history of the geophysical methods for the useful minerals prospecting in the western region of Ukraine: first — from 1892 to 1941 — origin of the geophysical methods; second — from 1945 to 1985 — rapid development and widely using of the different geophysical methods for the prospecting of the useful minerals first of all oil and gas; third — from 1986 to present — decreasing of the scope of geophysical investigations as a result of economic abatement and non attention of the authorities of the state and appropriate Ministry to the problems of the development of the mineral resources of Ukraine. The history of the methods of the field geophysical surveys: seismic, gravity, electromagnetic and also the methods of the processing of information is characterized. It is shown the perspectives of the development of the geophysical investigations in Ukraine as a whole and in western Ukraine as a part.В історії розвитку геофізичних методів розвідки корисних копалин у західному реґі- оні України виділено три етапи: перший — з 1892 р. до 1941 р. — зародження гео- фізичних методів; другий — з 1945 р. до 1985 р. — бурхливий розвиток і широке за- стосування різних геофізичних методів для пошуків і розвідки корисних копалин, насамперед нафти і газу; третій — з 1986 р. до 2003 р. — зменшення обсягів геофі- зичних досліджень унаслідок економічної кризи і неналежного ставлення керівницт- ва держави і галузі до розвитку мінерально-сировинної бази України. Охарактеризо- ваний розвиток методів польової геофізики: сейсморозвідки, гравірозвідки, електро- магнітних методів, а також машинного опрацювання геофізичної інформації. По- казана перспектива розвитку геофізичних досліджень в Україні взагалі і в західному реґіоні зокрема.
The history of the geophysical methods of the prospecting of useful minerals in the Western region of Ukraine